The Greek tragedy: Narratives and imagined futures in the Greek sovereign debt crisis - Jens Beckert; H. Lukas R. Arndt (Max Planck Institute for the Study of Societies, 2024)
Between 2009 and 2015 Greece underwent a profound sovereign debt crisis that led to a serious political crisis in Europe and the restructuring of Greek debt. We argue that the prevalence of negative narratives about the future contributed to the changes in spreads of Greek bonds during the crisis. We support our argument by presenting results from text mining a corpus of 9,435 articles from the Financial Times and the Wall Street Journal. Based on sentiments and a machine learning model predicting future reference, we identify newspaper articles which generate negative and uncertain outlooks for the future in the expert discourse. We provide evidence from time series regression analysis showing that these negative imagined futures have explanatory power in models estimating spread development of Greek vs. German sovereign bonds. We suggest that these findings provide good evidence for the relevance of "imagined futures" for investors' behavior, and give directions for an innovative contribution of sociology to understanding the microfoundations of financial crises. – – Zwischen 2009 und 2015 durchlebte Griechenland eine tiefgreifende Staatsschuldenkrise, die zu einer schweren politischen Krise in Europa und zur Umstrukturierung der griechischen Schulden führte. Wir argumentieren, dass die Prävalenz negativer Narrative über die Zukunft zu den Veränderungen der Spreads griechischer Anleihen während der Krise beigetragen hat. Zur Untermauerung dieser These präsentieren wir die Ergebnisse der Textanalyse eines Korpus von 9.435 Artikeln aus der Financial Times und dem Wall Street Journal. Auf der Grundlage von Sentiments und einem maschinellen Lernmodell zur Erkennung von Zukunftsvorhersagen identifizieren wir Zeitungsartikel, die negative und unsichere Zukunftsaussichten im Expertendiskurs erzeugen. Wir zeigen anhand von Zeitreihen-Regressionsanalysen, dass diese negativen Zukunftsvorstellungen Erklärungskraft in Modellen zur Schätzung der Spread-Entwicklung von griechischen gegenüber deutschen Staatsanleihen haben. Diese Ergebnisse liefern Evidenz für die Relevanz imaginierter Zukünfte für das Verhalten von Anlegern und ermöglichen einen innovativen Beitrag der Soziologie zum Verständnis der Mikroebene von Finanzkrisen.
hdl:21.11116/0000-000F-60D9-0
Keywords: 300; bond spreads; economic sociology; financial markets; Greek debt crisis; imagined futures; sentiment analysis; sovereign debt; valuation; Anleihen-Spreads; Bewertung; Finanzmärkte; griechische Schuldenkrise; imaginierte Zukünfte; Staatsverschuldung; Sentimentanalyse; Wirtschaftssoziologie